2017
DOI: 10.5812/numonthly.12431
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of YKL-40 Serum Level in Patients with Type 1 Diabetes and Its Correlation with Their Metabolic and Renal Conditions

Abstract: Background: The main indicator of long-term glycemic control in type 1 diabetes and its complications is glycosylated hemoglobin (HbA1c). Considering that there are little studies on the correlation of YKL-40 with HbA1C in type 1 diabetes, we evaluated such correlation to suggest YKL-40 as both diagnostic and prognostic marker of type 1 diabetes poor control and nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…And our study, with more strong power, con rm that patients with DM have signi cantly higher levels of YKL-40 compared with healthy controls. Some studies also show that YKL-40 levels are positively associated with diabetes duration [26,29] and glycated hemoglobin (HbA1c) [30][31][32]34,37]. It seems that YKL-40 might be a good metabolic indicator of DM.…”
Section: Sensitivity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…And our study, with more strong power, con rm that patients with DM have signi cantly higher levels of YKL-40 compared with healthy controls. Some studies also show that YKL-40 levels are positively associated with diabetes duration [26,29] and glycated hemoglobin (HbA1c) [30][31][32]34,37]. It seems that YKL-40 might be a good metabolic indicator of DM.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…It seems that YKL-40 might be a good metabolic indicator of DM. However, some nd that there is no signi cant association between YKL-40 levels and HbA1c [26,28,29]. Therefore, studies with more DM patients need to be performed in the future.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…In addition, studies by Lorbeer et al [23] and Pérez De Ciriza et al [24] demonstrated higher circulating concentrations of TIE2 and FGF-23 in T2DM groups and T1DM groups, respectively. CHI3L1 has also been investigated in the setting of T1DM [25] and T2DM [26], showing increased concentrations in both disease groups. Though little literature was found on AGRP and FS being investigated in CVD population, the study conducted by Fujikawa et al [27] showed that increased ARGP mRNA transcription can cause higher AGRP level in T1DM mice to induce obesity.…”
mentioning
confidence: 99%
“…The great majority of studies (22 studies) included in our meta-analysis provided data of HhA1c values. In some studies, HbA1c values were higher than upper limits of normal range, but 5 studies [23-25, 27, 30] showed that YKL-40 levels are positively correlated with HbA1c, while 3 studies [19,21,22] did not show any correlation. Therefore, although YKL-40 is also an inflammatory cytokine, the relationship between hyperglycemia and YKL-40 needs to be confirmed.…”
Section: Discussionmentioning
confidence: 99%